Restoring Connectedness in and to Nature: Three Nordic Examples of Recontextualizing Family Therapy to the Outdoors - Mattsson, Markus; Fernee, Carina Ribe; Lehmuslaakso, Kanerva; Lyytinen, Pekka (Frontiers in Psychology, 2022)
Mentalization-based family therapy and family rehabilitation represent a rich variety of approaches for assisting families with difficult interaction patterns. On the other hand, adventure therapy methods have been successfully used with families to offer them empowering experiences of succeeding together against difficult odds and to improve communication between family members. Further, the health promoting qualities of spending time outdoors are now well-established and recognized. The Nordic approach to mentalization-based family rehabilitation combines adventure, outdoor and systemic therapy. We provide three examples of nature-based family rehabilitation practices that are delivered as brief, multi-family psychological interventions taking place in nearby nature and aiming to support sustainable, systemic change. The current contribution is a description of clinical practice, not a systematic review or a formal evaluation. We propose that recontextualizing mentalization-based family rehabilitation to the outdoors can not only provide added health benefits, but also strengthen intra-familial attuned interaction and emotional connectedness. The outdoor adventure provides the families with embodied, multisensory experiences of verbal and, especially, non-verbal interaction that can be usefully examined through the lens of theory of mentalization. The concreteness of adventure experiences is particularly beneficial for families that have difficulties in verbal communication and / or utilizing executive functions, perhaps due to neuropsychiatric traits, intellectual disabilities or learning difficulties. Furthermore, outdoor adventure can support the participants’ connectedness to nature.